An analytical model of the heating and evaporation of bi-component wall film. (June 2019) - Liu, Hong; Yan, Yan'an; Jia, Ming; Cai, Chang; Zhang, Yanzhi
Abstract: A novel analytical model for the heating and evaporation of a bi-component fuel wall film is presented, in which the unsteady one-dimensional characteristics along the film thickness direction are considered. The energy equation and the species equation of the liquid phase are coupled with a model of predicting the local evaporation rate. Moreover, the variations of physical properties of each component corresponding to the local temperature are taken into account, thus the temperature evolution and species diffusion in the fuel film can be reproduced by the new model. The model is validated using previous experimental data and one-dimensional numerical simulation. The predicted film thickness evolution is in good agreement with the experimental data. The surface temperature and mass fraction of the components in the liquid film are also in good agreement with the numerical solutions. The results show that the mass fraction gradient exists inside the liquid film. This reflects the fact that the consideration of the finite diffusivity is important for accurate prediction of the wall film evaporation process. The results also indicate that the increase of the mass fraction of the more volatile component at the initial moment results in a decreased wall film lifetime and peak surface temperature.